Media and democracy in the Middle East
1 online resource.
Keywords: "This edited volume examines the current challenges to media freedom and democratization in the Middle East. The book revisits the relationship between media consumption and activism in the region, providing thorough analyses on the appropriation of social media for political engagement. Since the outburst and spread of what was known as the 'Arab Uprisings' in 2010, the political and media landscapes in the Middle East and North Africa region have changed dramatically. The initial hope of democratic change and governance quality improvements faded, as several regimes in the Middle East have strengthened their repressive tactics toward voices deemed critical of governments' practices, including journalists, bloggers, and activists. This book examines current challenges to media freedom, political participation and democratisation in the region while reassessing the dynamic relationship between media use and political engagement, amidst a complex political environment accompanied by a rapidly changing media landscape. The book's relevance will appeal to varied audiences, such as scholars and students of journalism, communication, political science, and Middle Eastern studies. It will also prove to be an invaluable resource for organizations dedicated to the research of political communication, media freedom and use patterns of non-traditional, or new, media"--